ZNF350 gene polymorphisms promote the response to Peg-IFNα therapy through JAK-STAT signaling pathway in patients with chronic hepatitis B - Guo, Jianhui; Guo, Shaoying; Chen, Tianbin; Zeng, Yongbin; Fu, Ya; Ou, Qishui (Frontiers in Immunology, 2024)
BackgroundThe varying individual responses to Pegylated interferon-α (Peg-IFNα) in patients with chronic hepatitis B (CHB) pose significant hurdles in treatment optimization, and the underlying mechanisms remain unclear.ObjectiveWe aimed to identify genetic polymorphisms influencing the efficacy of Peg-IFNα in patients with HBeAg-positive CHB, with the goal to predict Peg-IFNα response before treatment.MethodsWe employed an Asian Screening Array analysis involving 124 HBeAg-positive CHB patients treated with Peg-IFNα. We conducted assessment of immunological markers and mRNA expression of pivotal genes, establishing correlations with SNPs, functional genes of SNPs, and efficacy of Peg-IFNα therapy. In vitro experiments were performed to verify the functional involvement of the candidate SNPs.ResultsThe G allele presented in rs2278420 and rs6509607 were significantly more common in patients who achieved a complete response (CR) compared to those who had a suboptimal response (SR), and linked to an increased rates of HBeAg loss following Peg-IFNα treatment (all p < 0.05). Additionally, the mRNA level of ZNF350 varied notably across different genotypes of both SNPs as determined by eQTL analysis, and showed higher expression in patients achieved a SR (all p < 0.05). In vitro investigations with IFNα stimulation showed that the mRNA level of SOCS3 was elevated in patients with rs2278420 genotype AA, similarly, mRNA levels of PKR, STAT2, SOCS1, SOCS3, PIAS1, PTPN6 and TRIM8 were heightened in patients with rs6509607 genotype AA compared to those with genotypes (AG+GG) (all p < 0.05).ConclusionThe G allele of rs2278420 and rs6509607 were associated with mRNA level of ZNF350, with an increased probability of Peg-IFNα response in HBeAg-positive CHB patients, likely through the modulation of JAK-STAT signaling pathway.